EXPRESSION OF CONNOTATION THROUGH NONVERBAL ELEMENTS IN CHILDREN’S COMMUNICATION - Kurbanova, Munavvara Abdujabbarovna (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the pragmatic essence of connotation and its reflection in various fields of science. It features children related gestures and facial expressions. The article explores the functions of nonverbal means such as compacting speech, filling it with content, making it effective, and expressing a valuation attitude commonly used in children’s communication. It is scientifically justified that paralinguistic means helps us to overcome communicative-pragmatic barriers that arise in perceptual activity.While nonverbal units serve as a means of communication, they do not always produce speech connotations. Children's heads and handsinvolved non-verbal speech patterns are evidenced by examples to be the reaction and the display for child’s maltreatment. Their skillful expression in fiction helps to increase the text's influence, and illustration of preschool children’sdissatisfaction with an adult or a peer.